PERANAN ASAS KESEIMBANGAN DALAM MEWUJUDKAN TUJUAN PERJANJIAN - Niru Anita Sinaga; Tiberius Zaluchu (JURNAL ILMIAH HUKUM DIRGANTARA, 2017)
Man in fulfilling his various interests perform various ways, one of them by making a covenant. It is therefore necessary to understand important matters relating to a treaty, such as: What is the agreement, the terms of the agreement, the principles of the agreement, the object of the agreement, the terms of the agreement, the form of the agreement, the parties involved, the right and the obligations of the parties, the structure and the anatomy of the agreement, the settlement of disputes and the termination of the agreement. Article 1313 of the Civil Code states: The Covenant is an act by which one or more persons commit themselves to one or more persons. In general, the agreement is: The parties' agreement on something that gives birth to a legal relationship, creates rights and obligations, if not executed as the promised will impose sanctions. In order for what is promised to run well then required a regulating rule, called the law of agreement. The purpose of the treaty is to protect the parties in the event of future problems, order, is used as the basis for its settlement or legal certainty so as to create justice for the parties. In the making of the treaty, several important matters must be considered, among others: the terms of the validity of the agreement, the principles of the contractual law, the consequences of the law of agreement and the termination of the agreement. One of the most important principles in the agreement is the principle of equilibrium. However, in practice it is often not in accordance with the objectives of the agreement, among others: The existence of protection for the parties, the creation of justice, order, and legal certainty. The discussion in this research is about: What things should be considered or fulfilled to realize the achievement of the purpose of the agreement and How the role of the principle of balance in realizing the purpose of the agreement. The method used is normative juridical. In the event of a dispute concerning the treaty, it should be settled not only based on what is written in the agreement but taking into account the principles contained in the treaty law, especially the principle of equilibrium. Keywords: Balance Principle and Objectives of the Agreement